Identification of the wood-borer and the factors affecting its attack on Caryocar brasiliense trees in the Brazilian Savanna - doi: 10.4025/actasciagron.v33i4.8629 (Acta Scientiarum. Agronomy, 2011)
The objectives of this work were to identify the wood-borer of the trunk of Caryocar brasiliense Camb. (Caryocaraceae) and the effects of tree size, chemical and physical soil attributes, and floristic diversity in its attack. The wood-boring caterpillar of the trunck of C. brasiliense belongs to the family Cossidae (Lepidoptera). The number of pupae and the amount of sawdust produced by the wood-borer per tree was higher in the pasture 1 of Montes Claros and pasture in Ibiracatu than in the other four areas (pastures and savanna in Montes Claros and savanna in Ibiracatu). The number of pupae and the amount of sawdust was highest in the trunks of trees with diameters having a breast height (DBH) more than 30 cm. This may explain the severity of attack in the areas mentioned above, which contain a higher percentage of plants with DBH> 30 cm. The soil properties also positively associate with higher attack of the wood-borer on trees when the soil is rich in potassium, calcium, magnesium, sum of bases, capacity of cationic exchange, and organic matter, while there was a negative correlation between attack and fine sand content. Systems with less floristic diversity, particularly trees of other species, may concentrate the attack of the wood-borer in the trunks of C. Brasiliense trees.